The role of food quality for zooplankton: remarks on the state-of-the-art, perspectives and priorities - GULATI, RAMESH; DEMOTT, WILLIAM (Freshwater biology, 1997)
1. This paper summarizes the salient features of the contributions to the workshop on The Role of Food Quality for Zooplankton. In this paper we attempt critically to evaluate our present knowledge in the light of new studies. 2. For the growth and reproduction of zooplankton, the existing literature considers two main limiting factors in the diet, i.e. phosphorus (homeostasis theory) and fatty acids. Nevertheless, interpretations and opinions regarding the importance of these two factors are the subject of controversy in the literature. No attempts have been made to link these two potentially limiting factors, let alone give a coherent view based on the mechanisms behind limitation. Aquaculture studies provide some direct evidence of the importance of the long‐chained poly unsaturated fatty acids (PUFA) for zooplankton. The presence of PUFA in phytoplankton is reported to affect the growth rates of zooplankton significantly. 3. Field data on carbon and phosphorus indicate a greater constancy of the C : P ratios of zooplankton than of their food. Empirical data and modelling studies suggest that zooplankton, especially Daphnia spp., may maintain nutrient homeostasis by incorporating a greater proportion of the limiting nutrients ingested and releasing more of nutrients in excess supply. The need for conserving nutrients in short supply increases with the increase in growth rates. 4. Phosphorus certainly influences zooplankton food directly. Direct supplementation of the P‐insufficient algal diet with PO4‐P alone discernibly improves the growth in daphnids. It is highly plausible that P limitation and fatty acid limitation are not mutually exclusive alternatives. The two, separately or in conjunction, can control growth of at least some lake zooplankters, especially daphnids. 5. Besides a shortage of nutrient (P), other environmental factors (irradiance, UV‐radiation, temperature) can also adversely affect the zooplankton diet, including its digestibility and assimilation efficiency. 6. It is not yet clear if PUFA deficiency in the diet is in some way related to or caused by P deficiency. It is, however, now known that the EPA (eicosapentaenoic acid, 20 : 5ω3) content of certain algae is markedly reduced under P‐limitation and that it differs significantly among the different taxonomic groups of phytoplankton. Diatoms and flagellates are generally considered as good‐quality foods because of their high EPA content. On the contrary, cyanobacteria are low‐quality food, having both low EPA and P content. 7. Recent experiments reveal that the relative importance of fatty acids for daphnids increases with a decreasing C : P ratio in the food, i.e. if P is no longer limiting, and vice versa. For daphnids, there is possibly a switch between P‐limitation and PUFA limitation at intermediate C : P ratios. At higher C : P ratios, P is more important but at lower ratios PUFA are more crucial for growth and reproduction. 8. Lastly, the accumulating evidence for P limitation is stronger than that for fatty acid limitation.